2006
DOI: 10.1111/j.1540-8191.2006.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Swan-Ganz Catheter-Induced Severe Complications in Cardiac Surgery: Right Ventricular Perforation, Knotting, and Rupture of a Pulmonary Artery

Abstract: The incidence of serious Swan-Ganz catheter complications in our patient population is comparable to the incidence reported in the literature. Based on these results the use of Swan-Ganz catheters in cardiac surgery is still justified since the rate of associated serious complications is extremely low. Despite the rare occurrence of serious complications and the infrequent fatal outcomes, the benefit of its use in selected cases of cardiac surgery overweight its associated complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 21 publications
0
56
0
4
Order By: Relevance
“…During electrophysiological studies, circular mapping catheters have been trapped within the mitral valve apparatus, and guidewires have been trapped within coronary angioplasty hardware during percutaneous coronary interventions [5][6][7]. Catheters may knot intravascularly, precluding easy decannulation [8,9]. Shimoike et al reported entrapment of a guidewire within the Chiari network, and Upport et al reported 4 cases of entanglement of guidewires within IVC filters [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…During electrophysiological studies, circular mapping catheters have been trapped within the mitral valve apparatus, and guidewires have been trapped within coronary angioplasty hardware during percutaneous coronary interventions [5][6][7]. Catheters may knot intravascularly, precluding easy decannulation [8,9]. Shimoike et al reported entrapment of a guidewire within the Chiari network, and Upport et al reported 4 cases of entanglement of guidewires within IVC filters [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic removal of migrated intraluminal mesh has been described. 2 We report the successful endoscopic retrieval of migrated intraluminal mesh followed by stenting.…”
Section: Disclosurementioning
confidence: 99%
“…69 When the PAP wave form cannot be obtained despite advancing the PAC beyond 60-70 cm, knotting of pulmonary catheter should be suspected. The use of fluoroscopy can reduce the risk of knotting.…”
Section: Complicationsmentioning
confidence: 99%